The Effect of Centrifuge Duration on Fat Graft Survival - Demirel, Oguzhan; Karakol, Percin; Bozkurt, Mehmet; Tuglu, Mehmet Ibrahim (Indian Journal of Plastic Surgery, 2022)
Background Although fat grafts are widely used for reconstruction and aesthetic purposes, their survival rates differ significantly. Centrifugation is one of the methods used to increase the survival of fat grafts. However, experimental studies examining the long-term outcomes of centrifugation duration are currently limited. Thus, in the present study, the effects of centrifugation duration on the survival of fat grafts were assessed using an animal model.Methods Thirty Sprague Dawley rats were included in the study and fat grafts were obtained from each specimen by excision from inguinal fat pads. Preparation protocols were administered as an en-bloc fat graft in Group 1, minced fat graft in Group 2, and fat graft centrifuged at 1,054 ×g for 2 minutes, 3 minutes, and 4 minutes in Group 3, 4, and 5, respectively. After 12 weeks of follow-up, grafts were harvested and were subjected to histopathological evaluation based on an established scoring system.Results En-block fat grafts were associated with necrosis, fibrosis, inflammation, vacuole formation, and alterations in adipocyte morphology. Among the three centrifugation groups, Group 3 demonstrated the best adipocyte viability and vascularity. However, graft weights decreased in all experimental groups.Conclusion The centrifugation process may have positive effects on adipocyte survival by means of purifying the fat graft and increasing adipocyte concentration. When the centrifugal durations were compared, 3-minute centrifuge yielded the most favorable results.
Keywords: adipose; centrifugation; graft; duration; survival